Analysis of Accountability and Transparency in the Management of APBDes in Sidoarjo Regency - Dina Rofita; Nurasik Nurasik; Imelda Dian Rahmawati; Sigit Hermawan (Indonesian Journal of Cultural and Community Development, 2022)
This study is to determine the accountability and transparency of the village income and expenditure budget. This research was carried out in Kedungsolo Village, Porong District which was the object and used the 2021 fiscal year which will be the object of research. Qualitative is the method used and primary and secondary data is the source of data to be used which is obtained from documents. Informants in this study were the village head, treasurer, secretary, and the Village Consultative Body (BPD). The results of this study indicate that the APBDes management has implemented the principle of Accountability and the principle of Transparency in accordance with the applicable law which is posted around the front of the Balai Desa office.